Evaluation d’impact des programmes radiophoniques de AICCRA-Sénégal: Connaissances, pratiques agro-écologiques et revenus - Thiaw, Moussa; Diouf, Mouhamed Abdoul; Worou, Nadine; Camara, Boubacar; Wane, Abdrahmane (International Livestock Research Institute, 2025)
This study assesses the impact of AICCRA's radio programs on the knowledge, attitudes, agro-ecological practices, and incomes of rural producers in Senegal, within the context of increasing climate risks. By disseminating relevant and tailored climate information through multilingual broadcasts, the programs have enhanced farmers' understanding of climate risks, including precipitation, temperature fluctuations, and seasonal management. The results reveal a significant knowledge gap between beneficiaries and non-beneficiaries of the AICCRA radio programs in terms of climate-smart agriculture (CSA) practices and improved varieties. Specifically, 59.44% of beneficiaries have acquired knowledge on CSA practices, compared to only 40.56% of non-beneficiaries, demonstrating a positive impact of the radio programs on raising awareness of sustainable farming techniques adapted to climate challenges. The exposure to AICCRA radio programs has also led to the adoption of more resilient agro-ecological practices, with the most common being crop variety changes (53.36%), input modifications (49.16%), and the use of manure or compost (44.54%). However, practices such as mechanization (3.36%) and soil conservation (3.78%) remain under-adopted, primarily due to financial and material constraints. Furthermore, the radio programs have contributed to greater income diversification, particularly through livestock, trade, and crafts, with agricultural income slightly higher among beneficiaries. A reduction in pest attacks, especially on millet, cowpea, and peanuts, has also been observed, reflecting the direct impact of the programs on integrated pest management practices. This study demonstrates that the AICCRA-supported community radio initiative has significantly enhanced the resilience of producers to climate change by increasing their access to relevant information, positively altering their agro-ecological practices, and diversifying their income sources.